Clinical and bacteriological studies of a case of urosepsis caused by UOE-1 type extended-spectrum .BETA.-lactamase (ESBL)-producing Escherichia coli - Ohkuma Masanori; Muratani Tetsuro; Matsumoto Tetsuro; Higashi Shuichi; Gotoh Reiko; Kobayashi Tomoko (Japanese Journal of Chemotherapy, 2004)
A 89-year-old woman was found to have a high-grade fever. Escherichia coli were isolated in cultures of blood, urine, and feces. The result of antibiotic susceptibility against the isolates was predicted the presence of Extended spectrum β-lactamase (ESBL)-producing strain. We switched the antibiotics to imipenem (IPM) and fosfomycin (FOM). But, the patient developed a drug-induced exanthema as an adverse effect of IPM, however, and intravenous administration of FOM alone was continued for 2 weeks. FOM was effective, and the fever and abnormal laboratory findings improved immediately. The result of the sequence analysis of the ESBL revealed that the β-lactamase was UOE-1. The Not I restriction patterns of the chromosomal DNA of the pulse-field gel electrophoresis showed that the isolates from blood, urine, and feces were identical. We concluded that the urosepsis had developed as a result of urinary tract contamination by feces. 症例は89歳女性で40.7℃ の高熱がみられ, 同日の血液培養よりEscherichia coli (E. coli) が分離された。その後, 2月7日のカテーテル尿および2月8日の便からも同様の薬剤感受性を示すE. coliが分離された。治療抗菌薬はcefpirome+isepamicinの点滴静注を開始したが, 薬剤感受性試験の結果より, 基質特異性拡張型β-lactamase産生菌であると推定されたため, imipenem (IPM) +fosfomycin (FOM) の点滴静注に変更した。IPMは薬疹のため中止し, FOM点滴静注単独としたが体温, 炎症反応は速やかに改善した。β-lactamase遺伝子の塩基配列を決定したところ, UOE-1 typeと同定された。血液培養, 尿, 便から検出された株の染色体DNAのNot I切断パターンをパルスフィールドゲル電気泳動により比較したところ, 同一株であることが判明した。便由来の上行性尿路感染症からのurosepsisと考えられた。